2021
DOI: 10.1017/s0007114521002919
|View full text |Cite
|
Sign up to set email alerts
|

Potential of olive oil and its phenolic compounds as therapeutic intervention against colorectal cancer: a comprehensive review

Abstract: Colorectal cancer (CRC) is one of the major causes of death across the world and incidence rate of CRC increasing alarmingly each passing year. Diet, genomic anomalies, inflammation and deregulated signaling pathways are among the major causes of CRC. Because of numerous side effects of CRC therapies available now, researchers all over the world looking for alternative treatment/preventive strategy with lesser/no side effects. Olive oil which is part of Mediterranean diet contains numerous phenolic compounds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 167 publications
0
10
0
Order By: Relevance
“…Mutations and genetic modifications affecting DNA repair systems underlying the molecular mechanism of colorectal cancer development have been identified [ 130 , 131 ]. In recent years, higher consumption of olive oil, rich in polyphenols such as hydroxytyrosol, has been associated with low incidence and prevalence of cancer, including colorectal cancer [ 132 , 133 , 134 , 135 ]. The beneficial action of HT has been evaluated through in vitro studies on epithelial and carcinogenic cell lines: it has been demonstrated that HT was able to act on genes involved in apoptosis, such as Bax and Bcl-2, Caspase-3, and p53 [ 47 , 136 ].…”
Section: Role Of Ht In Other Gastrointestinal Diseasesmentioning
confidence: 99%
“…Mutations and genetic modifications affecting DNA repair systems underlying the molecular mechanism of colorectal cancer development have been identified [ 130 , 131 ]. In recent years, higher consumption of olive oil, rich in polyphenols such as hydroxytyrosol, has been associated with low incidence and prevalence of cancer, including colorectal cancer [ 132 , 133 , 134 , 135 ]. The beneficial action of HT has been evaluated through in vitro studies on epithelial and carcinogenic cell lines: it has been demonstrated that HT was able to act on genes involved in apoptosis, such as Bax and Bcl-2, Caspase-3, and p53 [ 47 , 136 ].…”
Section: Role Of Ht In Other Gastrointestinal Diseasesmentioning
confidence: 99%
“…as the most common saturated and unsaturated fatty acids founds in coconut oils that give antibacterial activity, but in our study have no effect, this result doesn't agree with others result [28] . So, their preparations have more applications as a natural anti-aging on the skin as a natural therapy, and medicine [29,30] . This may be due to lower of fatty acid from the fruit that used for extraction.…”
Section: 12-octadecadienoic Acid (Z Z)-c18h32o2mentioning
confidence: 99%
“…Thus, applying cold extraction methods will produce extra virgin olive oil (EVOO), which is recognized with high phenolic content and low free fatty acids ( 38 , 39 ). Extra virgin olive oil is known for its protective effect on CRC, conquers intestinal inflammation, and improves gut microbiota ( 40 42 ).…”
Section: Selected Components Of the Mediterranean Diet And Their Effe...mentioning
confidence: 99%